Abnormal foot angles has an association with ingrown toenail - (:unkn) unknown (WILEY, 2022)
Background Onychocryptosis, frequently termed ''ingrown toenail'' is a common foot problem in routine dermatology and orthopaedic clinical practice which leads to pain and disability. Although the aetiology of ingrown toenail is not well understood various associated risk factors have been identified with the pathogenesis. Material and methods This study was a retrospective investigation of 170 patients with hallux valgus and lateral border ingrown toenail of all stages. The patients were compared with a control group. The radiologic assessment in both groups included right hallux valgus angle, left hallux valgus angle, right first and second intermetatarsal angle, and left first and second intermetatarsal angle. Results There were 121 female and 49 male patients in the case group and 68 female and 32 male in the control group. The mean age of the case group was 41.1 years and 41.1 years in the control group. A statistically significant difference was found between the case and the control groups in terms of the right hallux valgus angle variable. Conclusion The abnormal hallux valgus angle and the abnormal intermetatarsal angle plays an important role in ingrown toenail aetiology. The X-rays of the feet should be performed to determine the susceptibility of the patients who are admitted to the hospital for ingrown toenail in order to prevent other toes ingrown toenail and for planning the treatment of the patients with an ingrown toenail.
Keywords: NAIL; RISK